Analysis of the Global Disease Burden of Down Syndrome Using YLDs, YLLs, and DALYs Based on the Global Burden of Disease 2019 Data - Bu, Qingting; Qiang, Rong; Cheng, Hua; Wang, Anmin; Chen, Huangtao; Pan, Zhenyu (Frontiers in Pediatrics, 2022)
Purpose: This study aimed to determine Down syndrome (DS) burden using years lived with disability (YLDs), years of life lost (YLLs), disability-adjusted life years (DALYs), and the trends in these parameters. Methods: We obtained the annual YLDs, YLLs, DALYs, and age-standardized rates (ASRs) of DS from 2010 to 2019 using the Global Health Data Exchange tool. The estimated annual percentage changes (EAPCs) in ASR were used to quantify and evaluate DS burden trends. Gaussian-process regression and Pearson’s correlation coefficient were used to assess the relationship between DS burden and socio-demographic index (SDI). Results: Global DALYs decreased by 2.68% from 2010 to 2019 but the ASR was stable, which was mostly explained by the stablity in the ASR for YLLs. The ASR of YLDs showed an increasing trend (EAPC = 1.07, 95% CI = 0.45 to 1.69). There was notable regional imbalance, with most of the DALYs or ASRs in areas with relatively low SDI. The DALY rates of DS were mostly from the YLLs of children younger than 1 year. Lower SDI areas tended to have higher DS burdens (ρ = –0.3, p < 0.001). Conclusion: This systematic analysis of the global disease burden of DS from 2010 to 2019 revealed that although the global DS DALY and YLL rate is stable, the YLD rate is inctreasing. And the DS burden varies significantly differences among regions or countries. The present results suggest that future strategies should focus on DS-related deaths in children younger than 1 year and the DS burden in low-SDI regions or countries, since this may be effective in further reducing DS burden.